Progression of Albuminuria Among Patients with Type 1 Diabetes Mellitus: A Long Term Observational Follow-up Study - Stratigou, Theodora; Vallianou, Natalia; Koutroumpi, Stavroula; Vlassopoulou, Barbara; Apostolou, Theofanis; Tsagarakis, Stylianos; Ioannidis, George (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background The purpose of the present study was to determine whether patients with DM1 have shown improvement, stabilization or deterioration of their urine albumin excretion levels during a close follow-up.Patients and Methods A cohort of 84 patients, 18–76 years of age, a median duration of diabetes of 24 years (1–50 years) and a median follow-up duration of 12 years (1–37 years) were included in the study.Results Among the 84 patients for whom we had UAE levels at the beginning and by the end of the study, mean glycosylated hemoglobin was statistically significantly decreased during the follow-up period, from 8.02±2.04–7.06±1.05% (p=0.036). Normoalbuminuria was present in 66 patients and remained so in 56 patients while 9 patients progressed to microalbuminuria and one patient to macroalbuminuria by the end of the study. Microalbuminuria was present in 15 patients: regression was observed in 8 patients, and progression in one patient. Regression of macroalbuminuria to microalbuminuria was noted in one patient and to normoalbuminuria was noted in one participant, too.Conclusions Improvement of glycemic control with close monitoring of DM1 patients together with the appropriate use ACE or AT2 inhibitors and statins, seems to exert nephron-protective potential and to delay or even reverse the presence of micro/macroalbuminuria. This long term follow-up study has demonstrated a statistically significant increase in serum HDLcholesterol levels. The study also revealed that intensively treated diabetes patients may show reductions in serum ALP levels. Whether this finding is related to diabetic nephropathy, NAFLD, or diabetic hepatosclerosis remains to be assessed in future trials.
Keywords: type 1 diabetes; microalbuminuria; alkaline phosphatase; diabetic hepatosclerosis; steatosis